2022
DOI: 10.29207/resti.v6i6.4525
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Media Data to Monitor Natural Disaster: A Multi Dimension Convolutional Neural Network Approach with Word Embedding

Abstract: Social media has a significant role in natural disaster management, namely as an early warning and monitoring when natural disasters occur. Artificial intelligence can maximize the use of natural disaster social media messages for natural disaster management. The artificial intelligence system will classify social media message texts into three categories: eyewitness, non-eyewitness and don't-know. Messages with the eyewitness category are essential because they can provide the time and location of natural dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This stage transforms the raw tweet data into more structured data. This study's stages are cleaning (Faisal et al, 2022), converting uppercase letters to lowercase (HaCohen-Kerner, Miller, & Yigal, 2020), and tokenization. Data cleaning involves removing unwanted characters and specific…”
Section: Preprocessing Datamentioning
confidence: 99%
See 2 more Smart Citations
“…This stage transforms the raw tweet data into more structured data. This study's stages are cleaning (Faisal et al, 2022), converting uppercase letters to lowercase (HaCohen-Kerner, Miller, & Yigal, 2020), and tokenization. Data cleaning involves removing unwanted characters and specific…”
Section: Preprocessing Datamentioning
confidence: 99%
“…Following this, the maximum length, mean, mode, and median values are derived from the statistical analysis of the word count. Consequently, a process known as word padding is implemented in order to ensure the uniformity of the word count across all messages within the given text data set (Faisal et al, 2022).…”
Section: Preprocessing Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A value of 0 serves to discard or forget a feature, while a value of 1 signifies that the feature should be stored within the network. The equations for the input gate are represented by equation ( 1), the forget gate by equation ( 2), and the output gate by equation (3).…”
Section: Lstmmentioning
confidence: 99%
“…In some cases of natural disasters, the presence of social media plays a crucial role in assisting every activity within the disaster management cycle. During the pre-disaster stage, social media can serve as an early warning before a disaster occurs [3]. Therefore, numerous studies have been conducted utilizing social media data as a social network sensor, as demonstrated by [4], which can function as a primary information dissemination platform.…”
Section: Introductionmentioning
confidence: 99%